2022
DOI: 10.3390/ijerph192215164
|View full text |Cite
|
Sign up to set email alerts
|

The Mediation Role of Safety Attitude in the Impact of Resilience on the Safety Behavior of Coal Miners in China

Abstract: Resilience can improve the adaptability of coal miners to high-hazard and high-stress environments. After facing setbacks or adversities, resilience can enable coal miners to recover from bad mental states and have an optimistic safety attitude and positive safety behaviors. However, how resilience affects safety behavior and the role of safety attitude in the relationship have not been clear. This study systematically reviewed previous research on resilience, safety attitude, and safety behavior. By recoverin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…The Theory of Planned Behavior (TPB) delineates the determinants of unsafe behavior by elucidating the interplay between attitude, intention, and action [20], which underscores the pivotal role of behavioral intention in shaping conduct, with safety attitude emerging as a key predictor of workers' intentions [21]. Thus, workers with positive safety attitudes are more inclined to work safely [22,23], and improving the safety attitudes of construction workers is a key factor in curbing unsafe behaviors [24]. Past research indicates a reciprocal relationship wherein safety attitudes not only influence safety behaviors positively but also undergo changes in response to behavioral outcomes, thereby forming a feedback loop [25].…”
Section: Koreamentioning
confidence: 99%
“…The Theory of Planned Behavior (TPB) delineates the determinants of unsafe behavior by elucidating the interplay between attitude, intention, and action [20], which underscores the pivotal role of behavioral intention in shaping conduct, with safety attitude emerging as a key predictor of workers' intentions [21]. Thus, workers with positive safety attitudes are more inclined to work safely [22,23], and improving the safety attitudes of construction workers is a key factor in curbing unsafe behaviors [24]. Past research indicates a reciprocal relationship wherein safety attitudes not only influence safety behaviors positively but also undergo changes in response to behavioral outcomes, thereby forming a feedback loop [25].…”
Section: Koreamentioning
confidence: 99%
“…7 Li et al conducted a questionnaire survey and found that safety attitude had a positive impact on safety behavior. 8 The poor safety attitudes of stakeholders are apt to lead to accidents. 9 Safety attitude reflects one's beliefs and feelings about safety policies, procedures, and practices, 10 and the attitude toward safety rules is an important predictor of safety climate.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Kashmiri et al pointed out that construction workers with a positive safety attitude had a stronger perception of safety risk . Li et al conducted a questionnaire survey and found that safety attitude had a positive impact on safety behavior . The poor safety attitudes of stakeholders are apt to lead to accidents .…”
Section: Introductionmentioning
confidence: 99%